Profile and Clinical Outcome of Children with Wilms' Tumor treated at a Tertiary Care Centre, India - Singh, Pritanjali; Singh, Dharmendra; Kumar, Bindey; Kumar, Prem; Bhadani, Punam Prasad (South Asian Journal of Cancer, 2022)
Background Wilms' tumor (WT) is the most common kidney tumor of the pediatric age group. The outcome of WT has improved due to the evolution of the treatment approach. A prospective observational study was conducted at All India Institute of Medical Sciences (AIIMS), Patna, to analyze the clinical profile along with the response and outcome to neoadjuvant chemotherapy according to the International Society of Pediatric Oncology (SIOP) protocol.Materials and Methods In total, 28 patients of WT visited the radiotherapy department from January 2015 to December 2019.Results Gender distribution showed male preponderance with a median age at diagnosis was 31 months. The abdominal lump was the dominant clinical presentation. The median volume of tumor at diagnosis was 359.48 mL (52.67–1805.76). Radiological staging workup shows that stage I, II, III, IV, and V were 7.1%, 39.3%, 39.3%, 10.7%, and 3.6% respectively. Neoadjuvant chemotherapy (NACT) was received by all patients. Also, 71.4% of patients showed > 50% of tumor volume reduction, while 28.6% of patients showed < 50% of tumor mass reduction. There was a statistically significant decrease in the tumor volume reduction following neoadjuvant chemotherapy (p < 0.001). There was a statistically significant stage down (p = 0.018) of the disease. Bivariate correlation studies showed recurrence was correlating statistically significantly with age < 24 months (p = 0.049), locoregional lymph nodes (p = 0.008), histopathological subtypes (p < 0.001), stage of the disease (p = 0.003), and risk groups (p < 0.001). In addition, 25% of patients developed recurrence during the median follow-up of 25 months. The median disease-free survival (DFS) and overall survival (OS) were not reached. The mean DFS and OS were 48 and 59.13 months, respectively. One- and 3-year DFS were 100% and 64.1%, respectively. One- and 3-year OS were 100% and 75% respectively.Conclusion Our study suggests that most of the patients presented at an advanced stage, thus rendering most of the cases difficult to undergo surgery at presentation. Neoadjuvant chemotherapy followed by surgery may be considered a well-balanced approach with a comparable response and survival outcomes.
Keywords: Wilms' tumor; outcome; survival; tertiary center in India